Investigating performance of a multi-subcarrier free space optic using log-normal channel model - Phuoc Quang Vuong; Dien Van Nguyen; Phuc Duy Vo; Quynh Quang Nhu Nguyen; Thai Quang Pham; Cuong Quoc Pham; Lanh Sy Nguyen; Hong Kiem Nguyen; Hung Tan Nguyen; Tuan Van Nguyen (Tạp chí Khoa học và Công nghệ)
The paper builds a computational model of a multi-subcarrier free space optic, a variant of the Subcarrier Intensity Modulation Free Space Optic (SIM-FSO), establishes algorithmic flowcharts, writes a computational program to investigate the system performance under various modulation methods, air turbulence levels and different numbers of subcarriers and data rates. In order to achieve a BER value of 10-4, FSO-SIM systems using BPSK, DPSK, 16-QAM, 64-QAM, 16-PSK and 64-PSK modulation techniques require SNR approximately values of 17 dB, 18 dB, 19.6 dB, 22.6 dB, 22.8 dB and 34.5 dB, respectively. When compared to other modulation techniques, DPSK performs better and comes very close to BPSK without requiring complex synchronous detection. The paper focuses on evaluating the performance of the SIM-FSO-DPSK system at various bitrates, subcarrier numbers, and with different diversity techniques to enhance transmission capacity and system performance.